The Impact of Japanese Popular Culture to Indonesian younger Generation:: A Case Study of PUNICO - Bunga Putra Bangsa; Sihombing, Lambok Hermanto (Humaniora: Journal of Indonesia Culture and Society, 2022)
The research probed into the influence of Japanese popular cultures on the Indonesian-younger generation in Cikarang, West Java, Indonesia. Japanese popular culture had been famed among the younger generation in Indonesia through the increasing popularity of anime. Indonesia, with 1.400 ethnic groups, had a variety of cultural diversity, but the younger generation seemed to be fonder of this foreign culture which in this case was Japanese popular culture. Through the expansion of this Japanese popular culture, Japanese culture could slip into it and could invade their local culture. This cultural expansion could have an impact on how the younger generation would preserve their local culture. Globalization also played a massive part in this cultural expansion; through the internet, it was easier to find something with foreign culture in it. The research used phenomenology research about the Japanese popular culture club of President University Nippon Community (PUNICO) in Cikarang. The research applied a qualitative approach with phenomenology methods. Data collection was done by asking the respondents questions regarding the matter. The respondents were ten members of PUNICO. The research result indicates that Japanese popular culture has been in the respondent's life long enough to change their habits and lifestyle. However, the respondents still care and have the volition to preserve their local cultures.Â